Remote Programming in Patients With Parkinson's Disease After Deep Brain Stimulation: Safe, Effective, and Economical - Nie, Pan; Zhang, Jibo; Yang, Xin; Shao, Yuyang; Zhang, Xiuming; Liu, Wen; Fu, Kai; Chen, Jincao; Zhang, Jie (Frontiers in Neurology, 2022)
Abstract Objective The purpose of this study was to evaluate the safety, efficiency, and cost expenditure of remote programming in Parkinson’s disease (PD) patients after deep brain stimulation (DBS). Methods 74 patients, who were operated with DBS in the Department of Neurosurgery, Zhongnan Hospital of Wuhan University between June 2018 and June 2020, were enrolled in this study. There were 27 patients in the remote programming group and 47 patients in the outpatient programming group. The clinical data, programming efficiency, adverse events, expenditure, and satisfaction were compared between the two groups. Results A total of 36 times of remote programming were performed in 27 patients in the remote programming group, of which 4 patients had mild adverse events during programming, and the adverse events disappeared within 1 week. The satisfaction questionnaire showed that 97.3% of patients were satisfied with the surgical effect. Patients in the remote programming group (88.9%) was more likely to receive long-term programming after DBS than patients in the outpatient programming group (74.5%). The Parkinsonism symptoms improved in both programming groups. The majority (18/27) of patients in the remote programming group lived away from the programming center, while the majority (27/47) of patients in the outpatient programming group lived in Wuhan, where the programming center was located (P=0.046). The cost per patient per programming was $43.5 in the remote programming group and $59.5 (56.0 – 82.7) in the outpatient programming group (P < 0.001). The median time cost for each visit was 30.0 min (25.0-30.0) in the remote programming group and 150.0 min (135.0-270.0) in the outpatient programming group (P<0.001). Conclusion Remote programming is safe and effective after DBS in patients with Parkinson’s disease. Moreover, it reduces expenditure and time costs for patients and achieves high satisfaction, particularly for patients living far from programming centers.